2013
DOI: 10.4028/www.scientific.net/amr.634-638.1347
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Magnetic Chitosan Hyamine Microspheres and Separation of Phenolic Acids from Rubus Chingii Hu

Abstract: About the separation methods of the traditional Chinese medicine components, there are common difficulties like time-consuming and compositions exist cross. Highly efficient way of separation is urgently needed in chinese medicines. The experiment adopted a better and specific 2-hydroxy-3-carboxy-N,N,N-trimethyl-propyl chitosan magnetic microspheres and separated the active anti-aging ingredients from Rubus chingii Hu. In this experiment, Fe3O4 nanoparticles were prepared by coprecipitation method. Microwave s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In 2013, Xie and coworkers obtained 2-hydroxy-3-carboxy-N,N, N-trimethyl-propyl (hyamine) chitosan magnetic microspheres by microwave synthesis and used them for the separation of the anthraquinone fraction (quite surprisingly not specifying the individual components of the same) of extracts of the Chinese medicinal plant Rubus chingii Hu (Rosaceae). 18 While the experimental details about the synthesis of microspheres and subsequent extraction are well detailed in this manuscript, the part related to the quantification of anthraquinones is devoid of any reference to individual compounds, the quantification of the anthranoid fraction was accomplished with less sensitive and significant techniques, like UV spectrophotometry and routinary chemical assays, and finally the effects of key physicochemical parameters affecting the overall extraction and pre-concentration steps were poorly investigated. So, results related to the study reported in the literature in 2013 by Xie and coworkers must be considered very preliminary, even if promising, and with several potential applications, pending the coupling of the (hyamine) chitosan magnetic microspheres-based SPE with largely more sensitive techniques for the identification of individual anthraquinones in different matrices.…”
Section: Coated Magnetic Nanoparticlesmentioning
confidence: 99%
“…In 2013, Xie and coworkers obtained 2-hydroxy-3-carboxy-N,N, N-trimethyl-propyl (hyamine) chitosan magnetic microspheres by microwave synthesis and used them for the separation of the anthraquinone fraction (quite surprisingly not specifying the individual components of the same) of extracts of the Chinese medicinal plant Rubus chingii Hu (Rosaceae). 18 While the experimental details about the synthesis of microspheres and subsequent extraction are well detailed in this manuscript, the part related to the quantification of anthraquinones is devoid of any reference to individual compounds, the quantification of the anthranoid fraction was accomplished with less sensitive and significant techniques, like UV spectrophotometry and routinary chemical assays, and finally the effects of key physicochemical parameters affecting the overall extraction and pre-concentration steps were poorly investigated. So, results related to the study reported in the literature in 2013 by Xie and coworkers must be considered very preliminary, even if promising, and with several potential applications, pending the coupling of the (hyamine) chitosan magnetic microspheres-based SPE with largely more sensitive techniques for the identification of individual anthraquinones in different matrices.…”
Section: Coated Magnetic Nanoparticlesmentioning
confidence: 99%
“…They can be used for kidney deficiency, frequent urination, impotence, premature ejaculation, and spermatorrhea (Xie et al. 2013 ). Its mature fruits have delicate taste, sweet and sour taste, rich nutrition, and are rich in amino acids, vitamins.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the content of anti-aging substances SOD and trace element Se is higher than that of existing cultivated and wild fruits, which have high nutritional value and medical health care effect (Xie et al. 2013 ). The World Food and Agriculture Organization (FAO) recommends them as the third generation of fruits in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its rich nutritional and medicinal value, R. chingii has been frequently used in traditional Chinese medicine (TCM) for centuries (Liu and Niu, 2014). The medical properties of R. chingii have been mentioned in many landmark Chinese medical monographs, such as “Compendium of Materia Medica,” “Bencao Mengquan,” “Leigong Paozhi Lun,” and “Qianjin Yi Fang.” According to the theory of traditional Chinese herbal medical science, R. chingii is commonly used as a tonic for the treatment of enuresis, kidney deficiency, impotence and prospermia, frequency of micturition, spermatorrhea, and other illnesses (Xie et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%